The Development of English and Spanish Among Children in Immigrant Families in the United States - Hoff, Erika (Pensam Educ, 2018)
The variable language skills of children from immigrant families create challenges for families, teachers, and policy makers. A first step toward meeting those challenges is to understand the factors that influence language development in children who hear a language other than the country’s majority language at home. We present findings from analyses of longitudinal data on children in immigrant families in the United States that contribute to that understanding. Our findings support four broad conclusions: (1) Children who are exposed to two languages simultaneously will lag behind monolingual children in their rates of single language growth. This is the normal result of distributed language exposure. (2) Language exposure provided by native speakers is more supportive of language growth than exposure provided by nonnative speakers. Therefore, immigrant parents should be encouraged to interact with their children in the language that allows the richest, most meaningful conversations, not necessarily in the majority language. (3) Preschool attendance does not always provide support for majority language skill. Attention needs to be paid to the quality of language support provided in preschool classrooms if they are to benefit language growth. (4) Acquiring the heritage language does not interfere with acquiring the majority language. Rather, it is heritage language acquisition that is vulnerable.